Perempuan dan IMS : Perilaku Menjaga Personal Hygiene Organ Reproduksi pada Pekerja Seks Langsung di Indonesia - Rokhmah, Dewi; Nurwidyansyah, Shinta Dwi; Rif'ah, Erwin Nur (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2020)
Background: The localization of prostitution in Jember District has been closed permanently since 2007. It causes the hidden prostitution business that has been increasing in the street or as indirect sex work. This condition makes the limited access to provide information, condoms and STDs screening among female sex workers (FSWs).Â Besides using condom, washing reproductive organs are often conducted to prevent STDs. This study aims to explore the behavior of FSWs in washing and lubricating reproductive organs. Method: This is a qualitative research which involved 12 FSWs in three areas of ex-localization in South Jember, 5 pims and health staffs. Data were collected through indepth-interviews and observation of work areas. Thematic content analysis was employed to identify themes and patterns of data.Â Results: The behavior of genital hygiene among FSWs to keep healthy was relatively categorized not good. Beside low consistent in condom use, most of them wash their vagina using traditional herbs or soap. They also often drink traditional herbs to prevent STDs. Lack of knowledge and support from the pimps and health staffs to use condom during sex made them vulnerable from STDs. Changing panties routinely and avoid anal sex were practiced among FSWs to have safe sex.